CIRCULATION OF INDIAN OCEAN WATERS EAST OF MALDIVES DURING THE POST MONSOON PERIOD - Ramamirtham, C P (Indian Journal of Fisheries, 2011)
The circulation patterns in the Maldive region between the 71° and 80°Emeridians within the equator and 8°N are discussed. It is observed that a largecyclonic gyre exists in the northern regions and an anticyclonic one in the southernregion, mainly in the subsurface layers. These are supposed to be associated withdivergence and convergence phenomena occurring in the area. The influenceof the Maldive islands and the associated bottom topography in the formation ofthese circulation patterns is indicated.